Treating Depression and Depression-Like Behavior with Physical Activity: An Immune Perspective - Eyre, Harris A.; Papps, Evan; Baune, Bernhard T. (Frontiers in Psychiatry, 2013)
The increasing burden of major depressive disorder makes the search for an extended understanding of aetiology, and for the development of additional treatments highly significant. Biological factors may be useful biomarkers for treatment with physical activity (PA), and neurobiological effects of PA may herald new therapeutic development in the future. This paper provides a thorough and up-to-date review of studies examining the neuroimmunomodulatory effects of PA on the brain in depression and depression-like behaviours. From a neuroimmune perspective, evidence suggests PA does enhance the beneficial and reduce the detrimental effects of the neuroimmune system. PA appears to increase the following factors: interleukin (IL)-10, IL-6 (acutely), macrophage migration inhibitory factor, central nervous system-specific autoreactive CD4+ T cells, M2 microglia, quiescent astrocytes, CX3CL1 and insulin-like growth factor-1. On the other hand, PA appears to reduce detrimental neuroimmune factors such as: Th1/Th2 balance, pro-inflammatory cytokines, C-reactive protein, M1 microglia and reactive astrocytes. The effect of other mechanisms is unknown, such as: CD4+CD25+ T regulatory cells (T regs), CD200, chemokines, miRNA, M2-type blood-derived macrophages and tumour necrosis factor (TNF)-α (via receptor 2 (R2)). The beneficial effects of PA are likely to occur centrally and peripherally (e.g. in visceral fat reduction). The investigation of the neuroimmune effects of PA on depression and depression-like behaviour is a rapidly developing and important field.